Rede de interesses: produção, abastecimento, cabotagem e estradas (Espírito Santo, 1790-1831) - Enaile Flauzina Carvalho (2016)
Powered by land, river and sea routes, the internal supply market, between the 18th and 19th centuries, involved regions with specific characteristics and in scales of participation compatible with the production and commercial situation of each captaincy/province. The opening of new trade routes from the second half of the 1700s begins to draw the agricultural expansion projects and the communication between the interior and the coastline, aiming the economical development in the hinterland. To the state of Espírito Santo, the possibility to establish communication with the state of Minas Gerais, by the political discourse, represented the opening of trade routes with an increase of mercantile relations between both regions. However, the proposal did not consider the networks of socioeconomic relations settled by traders and producers from both states. It is considered that, within the temporal outline of this study, the networks of mercantile relations had already been established. The traders from Minas Gerais privileged the supply of the internal market by means of the trade with Rio de Janeiro. The approach of the research also considers that the relations established from Vitória, in Espírito Santo, in the beginning of the 19th century, with other coastlands featuring the ones in Rio de Janeiro and Bahia , allowed the consolidation of a local elite that controlled the credit network accessible to a great part of the population. To understand the socioeconomic framework present in Espírito Santo between the years 1790 and 1831 pervades the identification of men dedicated to business and rural activities. The credit network involving the availability of granting loans and sales on credit guaranteed the movement of buying and selling in the retail market. With regards to the marketing of the agricultural production and the consumption of imported goods by cabotage, producers and traders ensured the movement of merchandise.